독서의 정의적 영역 연구에 대한 체계적 문헌 분석 - 김라연; Kim¸ Rayeon; 최건아; Choi¸ Geon-ah; 박소희; Park¸ Sohee; 황인지; Hwang¸ Inchi; 장봉기; Jang¸ Bongee (독서연구, 2021)
본 연구의 목적은 2010년부터 2020년까지 발표된 독서 동기 관련 국내 선행 연구들에 대한 체계적 문헌 분석을 시행하여 독서의 정의적 영역에서 학술 논의가 진행되어 온 방식을 이해하고 추후 독서 동기 관련 연구가 나아갈 방향을 제시하는 것이다. 총 8단계에 걸친 체계적 문헌 분석 과정을 통해 총 124편의 논문을 대상으로, 이론적 배경 제시 및 학술 개념 정의 여부, 참여자 학교급 및 참여자 수, 양적, 질적 연구 방법 유형, 동기 검사의 방법[반응/비반응], 연구 초점 논의 여부에 대한 개별 코딩 및 교차 코딩을 시행하였다. 분석 결과, 첫째, 독서 동기 관련 국내의 연구의 약 70%가 기반이 되는 이론적 배경을 뚜렷이 제시하지 않고, 50% 정도의 연구들은 독서 동기 관련 학술 개념을 명확하게 제시하고 있지 않아, 이론적 기반을 강화할 필요가 있는 것으로 드러났다. 둘째, 초등 시기에 편중된 연구 대상을 확대할 필요가 있는 것으로 보인다. 셋째, 독서의 정의적 차원을 내밀하게 이해하기 위해서는 질적 연구 방법이 더욱 적극적으로 활용될 필요가 있다. 넷째, 독서 동기 검사가 반응 평가 방식에 지나치게 의존하고 있어 다양한 학생 특성을 반영할 수 있는 비반응 평가 방법의 개발이 요구된다. Affective aspects of reading play a crucial role in reading development and achievement. In order to guide future research and to extend our existing understanding of affective aspects of reading into classroom practice in South Korea, this systematic review presents an extensive analysis of prior studies of reading motivation, attitudes, efficacy, and self-concepts. Selection criteria resulted in the identification of 124 data-based articles published from 2011-2020. The elementary school students were studied the most frequently, and the most popular research method was quantitative methods using self-report surveys. In terms of the theoretical frameworks, only 21.8 of the studies reviewed provided clear theoretical backgrounds In addition, 33.9% of the studies did not provide clear conceptual definitions of the affective factors examined. Nearly 95% of the studies employed reactive assessments including surveys, interviews, where students are aware of the evaluation process. Findings highlight the complexities associated with defining the affective factors as well as the need for diverse methodological approaches to examining them in reading research.